Serapias ausoniae (Orchidaceae; Orchideae): a new species from southern Italy confirmed by morphological, cytological and molecular analyses - Gennaio, Roberto; Pellegrino, Giuseppe (Phytotaxa, 2021)
Serapias ausoniae, here described as a new species, is known only from the southern part of the Apulia, Italy. The new taxon is morphologically similar to S. parviflora but is larger than sympatric S. parviflora specimens. Serapias ausoniae is characterized by larger floral elements, in particular, the bract is longer ( 5.0 cm) and wider ( 1.5 cm) and the dimensions of epichile, hypochile, petals and sepals are on average 40–50% larger than S. parviflora. Karyological analyses showed that the new taxon is a tetraploid (2n = 72), whereas sympatric and allopatric S. parviflora specimens are diploids (2n = 36). Moreover, genetic analyses suggest that the new taxon is of autopolyploid origin.